Essentials of gifted assessment - Pfeiffer, Steven I. (Essentials of psychological assessment series, 2015)
"A comprehensive guide to identifying and supporting uniquely bright and talented learners. Early identification and intervention greatly benefits gifted students who may otherwise never realize their full potential. Essentials of Gifted Assessment is an evidence-based overview of what makes students gifted, how giftedness is best identified, and strategies for promoting achievement in high-ability students"...Back cover